2021
DOI: 10.3390/polym13152393
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Thin Films of Insoluble Polythiophene Prepared by the Friction Transfer Technique

Abstract: A thin film of unsubstituted polythiophene (PT), an insoluble conjugated polymer, with molecular chains uniaxially oriented in plane was prepared by the friction transfer method. The structure of highly oriented thin films of PT was investigated using grazing-incidence X-ray diffraction (GIXD), ultraviolet–visible (UV–vis) spectroscopy, and infrared (IR) spectroscopy. The polarized UV–vis and IR spectra and GIXD measurements showed the PT molecular chains were well aligned in parallel to the friction direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…S3 in SI, introduced alkyl substituents extend straight and parallel to the anthracene plane, and the two-plane angle between the anthracene plane and the next phenyl planes for each molecule is about 70°. Previous research has reported that DPA formed a herring-bone like packing structure; 21,22) however, diMe-DPA and diOct-DPA formed co-facial structures (Fig. 2).…”
Section: Single-crystal X-ray Diffractionmentioning
confidence: 87%
See 2 more Smart Citations
“…S3 in SI, introduced alkyl substituents extend straight and parallel to the anthracene plane, and the two-plane angle between the anthracene plane and the next phenyl planes for each molecule is about 70°. Previous research has reported that DPA formed a herring-bone like packing structure; 21,22) however, diMe-DPA and diOct-DPA formed co-facial structures (Fig. 2).…”
Section: Single-crystal X-ray Diffractionmentioning
confidence: 87%
“…Also, the obtained patterns matched those predicted by the single-crystal X-ray diffraction result previously reported. 22) On the other hand, several strong arc patterns along the meridian axis (∼Q z ) were obtained from the diMe-DPA film on the glass substrate, indicating out-of-plane orientation of the crystallites of the diMe-DPA inside the film [Fig. 3(b)].…”
Section: Gixd Measurementmentioning
confidence: 99%
See 1 more Smart Citation